Derivational suffixes as cues to stress position in reading Greek. (27th November 2016) - Grimani, Aikaterini; Protopapas, Athanassios
Abstract : Background: In languages with lexical stress, reading aloud must include stress assignment. Stress information sources across languages include word‐final letter sequences. Here, we examine whether such sequences account for stress assignment in Greek and whether this is attributable to absolute rules involving accenting morphemes or to probabilistic lexical information. Methods: Pseudowords were constructed to not resemble particular words and were suffixed with derivational morphemes associated with specific stress patterns, to be read aloud, presented either without a stress diacritic or with a diacritic congruent or incongruent with the suffix. Morphemes differed in whether or not there were stress competitors ending in the same letter sequences. Results: Stress was assigned consistent with the suffix in the absence of the diacritic, more so when there were no stress competitors in the lexicon. Conclusions: Results suggest a lexically based probabilistic mechanism taking into account pattern distributions rather than absolute rules based on the morphological accenting.